2021
DOI: 10.1093/cercor/bhab019
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Image Analysis of Apparent Brain Age Identifies Physical Fitness as Predictor of Brain Maintenance

Abstract: Maintaining a youthful brain structure and function throughout life may be the single most important determinant of successful cognitive aging. In this study, we addressed heterogeneity in brain aging by making image-based brain age predictions and relating the brain age prediction gap (BAPG) to cognitive change in aging. Structural, functional, and diffusion MRI scans from 351 participants were used to train and evaluate 5 single-modal and 4 multimodal prediction models, based on 7 regression methods. The mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 73 publications
(117 reference statements)
6
18
0
1
Order By: Relevance
“…The UKB results based on SVR instead of XGB are shown in Section S5, Supporting Information. In line with recent studies (Dunås et al, 2021;Liang et al, 2019), we found no evidence that choice of algorithm influenced the observed patterns: the effects of age range were highly comparable (Figures S11-S13). The trends for subsets with different sample size and age range were also highly comparable, but XGB showed more stable performance across the smallest sample fractions (Figure S14).…”
Section: Ukb Results Based On Svr Instead Of Xgbsupporting
confidence: 90%
See 1 more Smart Citation
“…The UKB results based on SVR instead of XGB are shown in Section S5, Supporting Information. In line with recent studies (Dunås et al, 2021;Liang et al, 2019), we found no evidence that choice of algorithm influenced the observed patterns: the effects of age range were highly comparable (Figures S11-S13). The trends for subsets with different sample size and age range were also highly comparable, but XGB showed more stable performance across the smallest sample fractions (Figure S14).…”
Section: Ukb Results Based On Svr Instead Of Xgbsupporting
confidence: 90%
“…The difference between an individual's brain‐predicted and chronological age ( brain age delta ) provides a proxy for deviations from expected age trajectories, and has been associated with clinical risk factors (Beck et al, 2022 ; Cole, 2020 ; de Lange, Anatürk, et al, 2020 ) as well as neurological and neuropsychiatric conditions (Cole et al, 2020 ; Cole, Marioni, Harris, & Deary, 2019 ; Franke & Gaser, 2019 ; Hajek et al, 2019 ; Han et al, 2020 ; Kaufmann et al, 2019 ; Kolenic et al, 2018 ; Rokicki et al, 2021 ; Tønnesen et al, 2020 ; Van Gestel et al, 2019 ). Brain age delta estimates have also been linked to biomedical variables and lifestyle factors in healthy population cohorts (Anatürk et al, 2021 ; Cole, 2020 ; Cole, Franke, & Cherbuin, 2019 ; de Lange et al, 2019 ; Dunås, Wåhlin, Nyberg, & Boraxbekk, 2021 ; Franke et al, 2020 ; Smith et al, 2020 ), and the overall evidence supports the use of brain‐predicted age as a surrogate marker for brain integrity and health (Cole et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, including detailed assessments of dietary routines, alcohol intake, and physical exercise is vital in order to better understand the complex processes at play. For example, physical activity has been associated with lower brain age ( Dunås et al, 2021 , Sanders et al, 2021 ) and higher grey and white matter measures ( Sexton et al, 2016 ), while excess alcohol intake is well documented in influencing liver and brain health ( Agartz et al, 1999 , Rehm et al, 2010 ). Lastly, the current sample is predominantly ethnic Scandinavian and Northern European, restricting our ability to generalise to wider populations, and future studies should aim to increase the diversity in the study population.…”
Section: Discussionmentioning
confidence: 99%
“…There are several sources of bias that may affect the performance of a brain age model. These include, among others, sex [ 4 , 12 , 16 , [35] , [36] , [37] , [38] , [39] ], body-mass index [ 26 , 34 , 40 ], physical exercise [ 4 , 35 , 41 , 42 ], substance use [ 20 , 26 , 35 , 43 ], and cognitive ability [ 4 , 34 , 37 , 41 , 44 ]. For clinical samples, studies commonly examine how medication [ 6 , 10 , 20 , 26 , 45 ], illness duration [ 6 , 14 , 15 , 20 , 43 , 45 ], and symptom severity [ 6 , 10 , 26 , 37 , 45 ] affect the brain-age gap.…”
Section: Methodological Basics Of Brain Age Predictionmentioning
confidence: 99%